2008
DOI: 10.1177/1545968308326632
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Randomized Clinical Trial Evaluating the Effectiveness of the Lokomat in Subacute Stroke

Abstract: For subacute stroke participants with moderate to severe gait impairments, the diversity of conventional gait training interventions appears to be more effective than robotic-assisted gait training for facilitating returns in walking ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
388
4
12

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 563 publications
(418 citation statements)
references
References 48 publications
14
388
4
12
Order By: Relevance
“…The RMS errors in these trials were always <2 lb while the forces were always within ±7 lb. In addition, we tested trolley tracking performance up to speeds exceeding 1.5 m/s with the performance being the best at speeds typical of those who have gait impairments following neurological injury [21]. Overall, the performance of both the custom-series elastic actuator and trolley tracking are well within our original design goals.…”
Section: Discussionmentioning
confidence: 95%
“…The RMS errors in these trials were always <2 lb while the forces were always within ±7 lb. In addition, we tested trolley tracking performance up to speeds exceeding 1.5 m/s with the performance being the best at speeds typical of those who have gait impairments following neurological injury [21]. Overall, the performance of both the custom-series elastic actuator and trolley tracking are well within our original design goals.…”
Section: Discussionmentioning
confidence: 95%
“…The Lokomat gait orthosis provides the advantage of reducing the burden on clinical staff during weight-supported gait training and has been found by some researchers to have advantages over conventional therapies [50][51]. By addressing important psychological aspects of mental engagement in technology-assisted therapies, innovations may be made that help bridge the gap found by some researchers with conventional therapies [52][53]. Our approach might help to improve some of the features of technology-assisted rehabilitation-taking a step toward meeting more of the needs of the patient and therapist.…”
Section: Resultsmentioning
confidence: 99%
“…A recent multisite clinical trial of several upper-limb robots found them comparable to dose-matched conventional therapy, but superior to usual and customary care in motor function scales at 36 weeks [41]. In contrast, two recent clinical trials of lower-limb robots found them inferior to conventional methods [42][43]. This finding suggests that the type of robot and the control modes used do affect outcome, and further studies are needed to optimize robotic approaches to movement therapy.…”
Section: Introductionmentioning
confidence: 38%
“…Furthermore, learning in TIFT was disjointed early in the training, with subjects often hitting the path walls, stopping and trying several strategies before determining the correct shoulder-elbow coordination needed to advance within the path. Nevertheless, for stroke rehabilitation, we believe further study into assistance modes such as TIFT is needed, given the recent negative findings in robots that have used the TD training mode [42][43] and the evidence that passive movement training does not improve motor control [82][83]. For example, Bluteau et al found that in a drawing task, haptic guidance with a position-based controller similar to our TD training mode was inferior to a force-based controller for motor learning [84].…”
Section: Discussionmentioning
confidence: 86%